Deconcentration and decentralization reforms in Cambodia : - Niazi, Tariq H. (Asian Development Bank, 2011)
This book includes many parts: overview of the emerging legal and regulatory framework, the institutional setting for deconcentration and decentralization reforms, intergovernmental financing and recent fiscal trends, policy and planning framework for implementing reforms, critical issues for reform,...